1983
DOI: 10.1161/01.cir.68.4.827
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic effects of adenosine-5'-triphosphate on atrioventricular reentrant tachycardia.

Abstract: The effects of adenosine-5'-triphosphate (ATP) on atrioventricular reentrant tachycardia (AVRT) were studied in 18 patients. Nine patients had AV nodal reentrant tachycardia and the remaining nine patients had AVRT with an accessory pathway for retrograde conduction. After electrophysiologic control study, ATP was administered (20 mg iv, rapid bolus) during sustained tachycardia and during right ventricular pacing (150 beats/min). ATP terminated the tachycardia within 16 sec of administration in eight of nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

1984
1984
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(20 citation statements)
references
References 19 publications
0
19
1
Order By: Relevance
“…12, 13 Belardinelli et al showed that ATP (5 mole) was almost degraded completely in one passage through the isolated perfused guinea pig heart and that only 2.5% of the infused ATP was recovered in the effluent as ATP. 14 These findings are in agreement with previous reports showing that 97-99% of infused ATP is hydrolyzed during a single passage through the coronary vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…12, 13 Belardinelli et al showed that ATP (5 mole) was almost degraded completely in one passage through the isolated perfused guinea pig heart and that only 2.5% of the infused ATP was recovered in the effluent as ATP. 14 These findings are in agreement with previous reports showing that 97-99% of infused ATP is hydrolyzed during a single passage through the coronary vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Paroxysmal supraventricular tachycardia ATP was first used for the acute therapy of paroxysmal supraventricular tachycardia (PSVT) in the late 1940s [651] (and see reference to earlier studies therein) and later by others [652][653][654][655][656][657][658]. ATP was shown to evoke transient tachycardia at low doses and to induce AV block at high doses [659,660].…”
Section: Arrhythmiasmentioning
confidence: 99%
“…The AHA recommendation for adenosine use is based on a number of factors, including its clinical use in all of the following clinical situations: 1) for all ages; 2) in hernodynamic instability, pregnancy, or preexcited SVT, 3) in wide-complex tachycardia, regardless of its arrhythmic origin; 4) in significant acute or chronic LV dysfunction; and 5) in the presence of other cardioactive medications. In each of these scenarios, verapamil would be either relatively or absolutely contraindicated.…”
Section: Recurrence Of Svt 17mentioning
confidence: 99%